Physician Experiences With High Value Care in Internal Medicine Residency: Mixed-Methods Study of 2003–2013 Residency Graduates. Issue 1 (2nd January 2018) - Ryskina, Kira L.; Holmboe, Eric S.; Shea, Judy A.; Kim, Esther; Long, Judith A.
ABSTRACT: Phenomenon : High healthcare costs and relatively poor health outcomes in the United States have led to calls to improve the teaching of high value care (defined as care that balances potential benefits of interventions with their harms including costs) to physicians-in-training. Numerous interventions to increase high value care in graduate medical education were implemented at the national and local levels over the past decade. However, there has been little evaluation of their impact on physician experiences during training and perceived preparedness for practice. We aimed to assess trends in U.S. physician experiences with high value care during residency over the past decade. Approach : This mixed-methods study used a cross-sectional survey mailed July 2014 to January 2015 to 902 internists who completed residency in 2003–2013, randomly selected from the American Medical Association Masterfile. Quantitative analyses of survey responses and content analysis of free-text comments submitted by respondents were performed. Findings : A total of 456 physicians (50.6%) responded. Fewer than one fourth reported being exposed to teaching about high value care at least frequently (23.6%, 106/450). Only 43.8% of respondents (193/446) felt prepared to use overtreatment guidelines in conversations with patients, whereas 85.8% (379/447) felt prepared to participate in shared decision making with patients at the conclusion of their training, and 84.4% (380/450) reported practicing generic prescribing. Physicians who completed residency more recently were more likely to report practicing generic prescribing and feeling well prepared to use overtreatment guidelines in conversations with patients ( p < .01 for both). Insights : In a national survey, recent U.S. internal medicine residency graduates were more likely to experience high value care during training, which may reflect increased national and local efforts in this area. However, being exposed to high value care as a trainee may not translate into specific tools for practice. In fact, many U.S. internists reported inadequate exposure to prepare them for patient discussions about costs and the use of overtreatment guidelines in practice.